A study of some virulence factors for Escherichia coli isolated from animal food and clinical cases in Babylon province. (Journal of the College of Basic Education, 2022)
145 isolates of Escherichia coli bacteria, 77 isolates from the feces of diarrheal patients of different age groups and both sexes were isolated and diagnosed from some hospitals in Babylon Governorate, and (33) isolates from samples of minced beef and (35) isolates from samples of homemade cheese. From different regions in Babylon province, and the isolates were diagnosed according to phenotypic and biochemical tests as well as using the API 20E system. Biofilm factor 109 isolate 75.17%, beta-lactamase factor 122 isolate 84.13%, alpha-haemolysin factor 66 isolate 45.51%.